1953
DOI: 10.1677/joe.0.0090224
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Action of Antithyroid Drugs: Results With Two in Vitro Tests

Abstract: 1. Two in vitro tests are described for measuring the inhibitory potency of antithyroid drugs on enzymic and non-enzymic oxidative iodination of protein; one, a milk enzymic iodination test, and the other an enzyme-free peroxide iodination test.2. Five recognized antithyroid drugs have been tested : 2-thiouracil, 2-carbethoxythio-methylglyoxaline, potassium thiocyanate, resorcinol and sulphathiazole. By means of the milk enzymic test they could be ranged in order of potency, as indicated by the molar concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1955
1955
2002
2002

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…Effect of NaSCN upon iodide metabolism of beef thyroid slices The results were presented in Table4 and Figure 2. At a concentration of 10-3M, NaSCN reduced the total uptake of I131, and the amount of inorganic Pitney and Fraser(1953)employing iodination test of milk-protein.…”
Section: Effect Of Nascn and Kscn Upon Oxidation And Phosphorylation mentioning
confidence: 93%
“…Effect of NaSCN upon iodide metabolism of beef thyroid slices The results were presented in Table4 and Figure 2. At a concentration of 10-3M, NaSCN reduced the total uptake of I131, and the amount of inorganic Pitney and Fraser(1953)employing iodination test of milk-protein.…”
Section: Effect Of Nascn and Kscn Upon Oxidation And Phosphorylation mentioning
confidence: 93%
“…The test procedure and the method of preparing the enzyme powder have been fully described by Pitney and Fraser (1953). The dry enzyme powder keeps satisfactorily in the refrigerator.…”
Section: Methods the Enzyme Testmentioning
confidence: 99%
“…A preliminary report by Pitney and Fraser (1953) showed that the potency of antithyroid drugs may be assessed by two in vitro tests, and that such drugs may differ in their modes of action. In this communication we report further observations with these tests.…”
mentioning
confidence: 99%
“…Lactation did not appear to be impaired by a 50% reduction in metabolic rate. Pitney & Fraser (1953) have investigated the mode of action of antithyroid drugs and conclude that thiouracil inhibits the iodinating enzymes, whereas another class of drug with antithyroid properties (e.g. resorcinol) removes iodine from combination with protein.…”
Section: Thyroonne and Thyroid-active Substancesmentioning
confidence: 99%